СТРУКТУРНА МОДЕЛЬ ПЕДАГОГІЧНОЇ ПІДГОТОВКИ СТУДЕНТІВ ДО ПРЕВЕНТИВНОЇ ДІЯЛЬНОСТІ З УЧНЯМИ ПОЧАТКОВОЇ ШКОЛИ (Педагогіка вищої та середньої школи, 2007)
In this article it is theoretically grounded the structure model of pedagogical raining the students ’ preventive activity with the pupils of the primary school and rended concrete its structure components of, realization of which positively gives influence on the quality of preparation of the pedagogical specialists.